2016
DOI: 10.1186/s12967-016-1064-9
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed high-dose dexamethasone modulates Th1-/Th2-chemokine imbalance in immune thrombocytopenia

Abstract: BackgroundChemokines and chemokine receptors play important roles in autoimmune diseases; however, their role in immune thrombocytopenia (ITP) is unclear. High-dose dexamethasone (HD-DXM) may become a first-line therapy for adult patients with ITP, but the effect of HD-DXM on chemokines in ITP patients is unknown. Our aim was to investigate the mechanism of pulsed HD-DXM for management of ITP, specifically regarding the chemokine pathways.MethodsTh1-/Th2-associated chemokine and chemokine receptor profiles in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Dexa was able to restore the inhibitory properties of ITP-MSCs on T-cells by reducing their viability. These data are in accordance with the well-identified primary role of GC in suppressing excessive T-cell [19] growth and in particular with the study of Buron et al, in which MSCs treated with Dexa are able to inhibit lymphocyte proliferation [33]. Interestingly, with CB 2 receptor stimulation we observed a more marked reduction of T-cell viability.…”
Section: Discussionsupporting
confidence: 93%
“…Dexa was able to restore the inhibitory properties of ITP-MSCs on T-cells by reducing their viability. These data are in accordance with the well-identified primary role of GC in suppressing excessive T-cell [19] growth and in particular with the study of Buron et al, in which MSCs treated with Dexa are able to inhibit lymphocyte proliferation [33]. Interestingly, with CB 2 receptor stimulation we observed a more marked reduction of T-cell viability.…”
Section: Discussionsupporting
confidence: 93%
“…In ITP patients, plasma levels of CXCL11 are increased, as well as gene expression of CXCL11 in PBMCs [60]. In this work, it is hypothesized that CXCL11 is an important chemoattractant for effector T cells involved in ITP, and indeed, in patients who responded to pulsed high-dose dexamethasone, CXCL11 expression was down-regulated [60].…”
Section: Discussionmentioning
confidence: 99%
“…In this work, it is hypothesized that CXCL11 is an important chemoattractant for effector T cells involved in ITP, and indeed, in patients who responded to pulsed high-dose dexamethasone, CXCL11 expression was down-regulated [60]. CXCL2 is chemotactic for neutrophils and elevated expression of CXCL2 has also been associated with many inflammatory and autoimmune diseases [61, 62].…”
Section: Discussionmentioning
confidence: 99%
“…This is also one of the immune regulation mechanisms of IL-17 (19,20). IL-12 is one of the most important regulators of Th0 cells differentiating into Th1 cells (21), and CXCL11 is a chemokine of Th1 cells (22). The results of this study showed that after 10 days of administration, model group of rats showed increased IL-17, IL-17R and Th17 levels in colon tissues, but showed significantly increased IL-12 and decreased CXCL11 levels when compared to control group.…”
Section: Discussionmentioning
confidence: 99%